Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2147/clep.s369908
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Diagnosis and Prognosis After Guillain–Barré Syndrome: A Population-Based Cohort Study

Abstract: Introduction It is unclear whether Guillain–Barré syndrome (GBS) can be a marker of a paraneoplastic syndrome. We examined whether GBS is associated with cancer and whether the prognosis of GBS patients with cancer differs from that of other cancer patients. Materials and Methods We conducted a population-based cohort study of patients diagnosed with GBS between 1978 and 2017 using Danish registry-data. Main outcome measures were cancer incidence and mortality after can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In contrast, the association between GBS and malignancy is still debated as Graus et al do not define it as a paraneoplastic syndrome in the absence of high-risk antibodies 9. A number of case reports described GBS in patients with an existing or later diagnosed malignancy12–25 and a small number of population-based studies have identified an increased risk of cancer in patients who developed GBS 8 26 27. Nevertheless, it is not clear whether these findings demonstrate an actual causal link or simply two separate concurrent diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the association between GBS and malignancy is still debated as Graus et al do not define it as a paraneoplastic syndrome in the absence of high-risk antibodies 9. A number of case reports described GBS in patients with an existing or later diagnosed malignancy12–25 and a small number of population-based studies have identified an increased risk of cancer in patients who developed GBS 8 26 27. Nevertheless, it is not clear whether these findings demonstrate an actual causal link or simply two separate concurrent diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Guillain-Barré syndrome (GBS) is an acute, immune-mediated polyradiculoneuropathy which, although not classically recognised as a paraneoplastic syndrome, has been reported to occur in association with malignancy 8. To our knowledge, there have been no reported cases of a GBS-like PNS in a patient with a diagnosis of small cell prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In SCLC‐associated paraneoplastic syndrome, Guillain–Barre syndrome (GBS) should be account for differential diagnosis of LEMS. 16 Both diseases have clinical manifestations of limb weakness and decreased reflexes. Weakness of LEMS normally spreads proximally to distally.…”
Section: Discussionmentioning
confidence: 99%
“…For involvement of the peripheral nerves or muscles, the clinical presentations may be similar to GBS (an acute inflammatory polyneuropathy), CIDP, autoimmune autonomic ganglionopathy, and inflammatory myopathy ( 11 14 ). A population-based cohort study in Denmark suggested that GBS patients had a three fold increased risk of cancer diagnosis in the first year of follow-up with an absolute cancer risk of 2.7% ( 15 ). Some cases with paraneoplastic neuromuscular disorders respond to immunosuppressants or immune modulators including IVIG ( 12 ).…”
Section: Discussionmentioning
confidence: 99%